Help-Seeking Behaviors Among Active-Duty Military Personnel: Utilization of Chaplains and Other Mental Health Service Providers. Issue 3 (2nd July 2016) - Morgan, Jessica Kelley; Hourani, Laurel; Lane, Marian E.; Tueller, Stephen
Abstract : Military chaplains not only conduct religious services, but also provide counseling and spiritual support to military service members, operating as liaisons between soldiers and mental health professionals. In this study, active-duty soldiers ( N  = 889) reported help-seeking behaviors and mental health. Using logistic regressions, we describe the issues for which soldiers reported seeking help, then outline the characteristics of those who are most likely to seek help from a chaplain. Of the soldiers who sought help from a chaplain within the previous year, 29.9% reported high levels of combat exposure, 50.8% screened positive for depression, 39.1% had probable PTSD, and 26.6% screened positive for generalized anxiety disorder. The participant's unit firing on the enemy, personally firing on the enemy, and seeing dead bodies or human remains predicted seeing a chaplain. Future research should examine ways to engage soldiers who have had more combat experiences with the chaplain community to address spiritual issues.